Chronic stress: a crucial promoter of cell apoptosis in atherosclerosis. Issue 1 (January 2020) - Meng, Ling-bing; Shan, Meng-jie; Yu, Ze-mou; Lv, Jian; Qi, Ruo-mei; Guo, Peng; Zhang, Yuan-meng; Gong, Tao
Objective: Chronic stress may lead to augmented incidence rates of coronary and cerebrovascular diseases associated with atherosclerosis. However, few studies have focused on the effect of chronic stress on atherosclerosis plaque formation. Therefore, this study was designed to directly evaluate how chronic stress affects atherosclerosis. Methods: Thirty rabbits were divided into three groups: the control group, balloon-injury operation + high-fat diet model group, and chronic stress + balloon-injury operation + high-fat diet model group. Physical and social stress were induced, and proteomic methods were applied to identify specific markers. Results: After protein determination, the chronic stress + balloon-injury operation + high-fat diet model group exhibited significant upregulation of the following apoptosis-related proteins: UBE2K, caspase 3, caspase 9, BAX, P53, and FAS. In particular, real-time polymerase chain reaction showed that the protein expression of caspase 9 was significantly downregulated in the stress group compared with the non-stress groups. However, the other proteins showed significantly increased expression in the stress group. Conclusion: Chronic stress may promote cell apoptosis in the physiopathologic process of atherosclerosis.